New Media Income Sources and Digital Media in Turkey: Business Models, Issues and Suggestions - Serpil Karlıdağ (Erciyes University, 2019)
In Turkey, the commercial press is faced with problems both economically and politically. Besides, the decline in sales and advertising revenues due to the influence of internet has led journalists to turn to the new fields. Many journalists lost their job in the commercial media organizations, have turned to the new field of production that digital media makes possible, consequently new different media organizations have started to operate. The goal is to find new models for production, distribution and consumption of content that show public good characteristics. Crowdfunding is also a viable option for financing non-profit media. In addition to creating income, reducing the expenses of journalism is also among the applied models. A small editorial staff, web designer and citizen journalists can distribute the content over the internet. Since the public support has been used in favor of governmental preferences, the press has often been punished for criticizing the government. Not being able to get a share of the advertisements distributed by the Press Advertisement Agency as well as the official advertisements of the state institutions are some of the main fines. In this context, state support, which is applied for the outside of the main stream media in other countries, seems difficult in Turkey. There are also donations made by national and international foundations and non-governmental organizations and some other resources. Therefore, the aim of this study is to examine the sources and expansions of digital newspapers and news sites such as T24, Bianet, P24, Diken, and Medyascope. For this purpose, the ownership structures and income sources of these organizations and the business models they apply will be discussed.